2015
DOI: 10.1186/s12913-015-1021-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a nurse-led, tailored stroke self-management intervention

Abstract: BackgroundCommunity nurses are well placed to promote and support stroke survivors to engage in self-management. The aim of this study was to develop a stroke self-management intervention that could be tailored towards stroke survivors’ self-management needs, goals and levels of activation, in the first year post-stroke.MethodsMixed method study, designed in accordance with the British Medical Research Council’s (MRC) guidance for the development and evaluation of complex interventions. The intervention was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 27 publications
0
44
2
Order By: Relevance
“…The fourth exemplar specifically explored the feasibility and acceptability of using PAM as a basis for guiding the provision of tailored self-management support for stroke survivors. 32 Tailored coaching is not widely used as yet in the UK and there is little published evidence on this although it does hold potential and is of growing interest to researchers, practitioners, service providers and commissioners given the need to be more cost effective with resource use. This data illustrated that although PAM was useful for gauging PAM levels across a group of stroke survivors, some found it challenging to complete and the stroke nurses delivering the intervention reported that it did not enable tailoring of appropriate care and support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth exemplar specifically explored the feasibility and acceptability of using PAM as a basis for guiding the provision of tailored self-management support for stroke survivors. 32 Tailored coaching is not widely used as yet in the UK and there is little published evidence on this although it does hold potential and is of growing interest to researchers, practitioners, service providers and commissioners given the need to be more cost effective with resource use. This data illustrated that although PAM was useful for gauging PAM levels across a group of stroke survivors, some found it challenging to complete and the stroke nurses delivering the intervention reported that it did not enable tailoring of appropriate care and support.…”
Section: Discussionmentioning
confidence: 99%
“…Exemplar 4 -This research project explored how the PAM could be used to tailor self-management support intervention for stroke survivors (3 months post stroke) in the community. 32 The intervention consisted of a tailored self-management action plan, incorporating an individualised assessment of stroke survivors' levels of activation (using the PAM), goal setting and motivational interviewing and the study reported on both stroke survivors'(n=6) and professionals' (n=5) perspectives of the intervention and the use of the PAM to guide the provision of self-management support. In this study, the PAM was not used as an outcome measure but rather a process tool to identify participant's level of activation and align the provision of tailored support towards that based on the underpinning theory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus is on supporting people to develop the capacity and confidence to manage the impact of their stroke in the context of their lives in a way that is meaningful and purposeful for them, and to 'be in charge' of their own self-management decision making [6][7][8][9]. Contemporary notions of SSM position it as a move away from the traditional perceptions of education-compliance with professionally driven treatment plans and goals, and a focus on function and level of impairment-because this does not 'fit' with how people with long-term conditions typically perceive their own engagement in self-management [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Healthcare organizations are expected to achieve the triple aim of providing quality care and improved health at a lower cost. 13 One approach to help reach the triple aim is more effectively engaging people in their own care.…”
Section: Significancementioning
confidence: 99%